Host Specificity of the Dickeya Bacteriophage PP35 Is Directed by a Tail Spike Interaction With Bacterial O-Antigen, Enabling the Infection of Alternative Non-pathogenic Bacterial Host - Kabanova, Anastasia P.; Shneider, Mikhail M.; Korzhenkov, Aleksei A.; Bugaeva, Eugenia N.; Miroshnikov, Kirill K.; Zdorovenko, Evelina L.; Kulikov, Eugene E.; Toschakov, Stepan V.; Ignatov, Alexander N.; Knirel, Yuriy A.; Miroshnikov, Konstantin A. (Frontiers in Microbiology, 2019)
Dickeya solani is a recently emerged virulent bacterial potato pathogen that poses a major threat to world agriculture. Because of increasing antibiotic resistance and growing limitations in antibiotic use, alternative antibacterials such as bacteriophages are being developed. Myoviridae bacteriophages recently re-ranked as a separate Ackermannviridae family, such as phage PP35 described in this work, are the attractive candidates for this bacterial biocontrol. PP35 has a very specific host range due to the presence of tail spike protein PP35 gp156, which can depolymerize the O-polysaccharide (OPS) of D. solani. The D. solani OPS structure, →2)-β-D-6-deoxy-D-altrose-(1→, is so far unique among soft-rot Pectobacteriaceae, though it may exist in non-virulent environmental Enterobacteriaceae. The phage tail spike depolymerase degrades the shielding polysaccharide, and launches the cell infection process. We hypothesize that non-pathogenic commensal bacteria may maintain the population of the phage in soil environment.